An Investigative Study of Code Mixing Among the EFL University Students in Universitas Sembilanbelas November Kolaka - Rohima Nur Aziza Al Hakim; Irda Novitasari (Tamaddun Life, 2020)
This research aimed to describe the types and the reason of using Code-mixing by the fifth semester students of English Language and Education Department of Sembilanbelas November Kolaka University in the classroom. The research used qualitative methods. The subject in this research was the fifth semester students of English Language and Education Department of Sembilanbelas November Kolaka University. This research was identified to determine the type and the reason of using code-mixing proposed by Suwito. The data were collected through audio recording and interview. In analyzing the data, the researcher transcribed, identified and classified. In analyzing the data, several steps were done, namely: transcribing, reading, and coding to choose and sort the sentences which were categorized as code mixing. Then, classifying and analyzing the sentence inti different types of code-mixing in the class room. The result indicated that there were 69 utterances of code-mixing used by the students of Sembilanbelas November Kolaka University at fifth semester in teaching and learning activity; 42 code mixing in the form of word insertion, 17 code mixing in the form of phrase insertion, 2 code mixing in the form of hybrid, and 8 code mixing in the form of clause. The study also showed that the reason of using code mixing in the class room which found on the conversation in the class room were; Role Identification which was determined by social condition and educational background; and Varian Identification which was determined by social prestige.